Oral and Written Shī‘ī Qur’ānic Elucidations in Twentieth-Century Indian Subcontinent: The Case of Sayyid al-‘Ulamā’ (d. 1988) - Zamir, Syed Rizwan (Islamic Studies, 2023)
Sayyid ‘Alī Naqī Naqvī (Ar. al-Naqawī, d. 1988), popularly known as Sayyid al-‘Ulamā’ and Naqqan Ṣāḥib, is widely regarded as the most prolific, influential, and popular Indian Shī‘ī ‘ālim of the twentieth century. Although the author of a multi-volume tafsīr, Faṣl al-Khiṭāb, which includes a long prolegomenon (muqaddimah), Naqvī’s Qur’ānic elucidations are hardly limited to this text alone; they are to be found throughout his vast corpus. In this article, I attempt an overview of Naqvī’s multi-faceted engagement with the Qur’ān by weaving together these interspersed elucidations. This will be in contrast to the common scholarly approach that focuses on tafsīr as the only Qur’ānic commentary tradition worthy of study in Muslim piety and religious thought. Illustrating how Naqvī engages with the Qur’ān will shed light not only on the relatively invisible and understudied subject of the Qur’ān and its exegesis within contemporary South Asian Shiism but also on the amply deliberated major themes of religious and communal concern in contemporary Shī‘ī South Asia.